Treatment efficacy of laser photothermal therapy using gold nanorods. (1st January 2013) - Manuchehrabadi, Navid; Toughiri, Raheleh; Bieberich, Charles; Cai, Hong; Attaluri, Anilchandra; Edziah, Raymond; Lalanne, Elaine; Johnson, Anthony M.; Ma, Ronghui; Zhu, Liang
In vivo experiments are performed to induce temperature elevations in implanted prostatic tumours in mice using 0.1 ml commercially available gold nanorod solution injected into the tumour. Tumour shrinkage studies and histological analyses of tumour cell death are conducted, and the equivalent minutes at 43°C (EM43 ) for inducing tissue thermal damage are estimated based on temperature elevations during the treatment. It has been shown that the laser heating of 15 minutes in the tumour tissue containing gold nanorods is effective to cause irreversible thermal damage to the tumours, with a low laser irradiance on the tumour surface (1.6 W/cm 2 ). The effectiveness of the heating protocol is demonstrated by tumour shrinkage to 7% of its original volume on the 25th day after the laser treatment and tumour necrosis events observed by histological analyses. The results are consistent with the EM43 distribution estimated by possible temperature elevations during the treatment.